Comorbidity of schizophrenia and social phobia - impact on quality of life, hope, and personality traits: a cross sectional study - Vrbova, Kristyna; Prasko, Jan; Ociskova, Marie; Holubova, Michaela (Neuropsychiatric disease and treatment, 2017)
OBJECTIVE: The purpose of the study was to explore whether the comorbidity of social phobia affects symptoms severity, positive and negative symptoms, self-stigma, hope, and quality of life in patients with schizophrenia spectrum disorders. METHODS: This is a cross-sectional study in which all participants completed the Internalized Stigma of Mental Illness (ISMI) scale, Adult Dispositional Hope Scale (ADHS), Liebowitz Social Anxiety Scale (LSAS), Beck Anxiety Inventory (BAI), Beck Depression Inventory-II (BDI-II), Positive and Negative Syndrome Scale (PANSS), Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q), Temperament and Character Inventory - Revised (TCI-R), and the demographic questionnaire. The disorder severity was assessed both by a psychiatrist (Clinical Global Impression Severity - the objective version [objCGI-S] scale) and by the patients (Clinical Global Impression Severity - the subjective version [subjCGI-S] scale). The patients were in a stabilized state that did not require changes in the treatment. Diagnosis of schizophrenia, schizoaffective disorder, or delusional disorder was determined according to the International Classification of Diseases 10th Revision (ICD-10) research criteria. A structured interview by Mini International Neuropsychiatric Interview was used to confirm the diagnosis. RESULTS: The study included 61 patients of both genders. Clinically, the patients with comorbid social phobia had the earlier onset of the illness, more severe current psychopathology, more intense anxiety (general and social), and higher severity of depressive symptoms. The patients with comorbid social phobia showed the significantly lower quality of life compared to the patients without this comorbidity. The patients with comorbid social phobia also had a statistically lower mean level of hope and experienced a higher rate of the self-stigma. They also exhibited higher average scores of personality trait harm avoidance (HA) and a lower score of personality trait self-directedness (SD). CONCLUSION: The study demonstrated differences in demographic factors, the severity of the disorder, self-stigma, hope, HA, and SD between patients with schizophrenia spectrum disorders with and without comorbid social phobia.
Keywords: hospitalizations; hope; quality of life; self-stigma; social phobia; personality traits; schizophrenia; onset